Application of Dance Movement Therapy to Stress Levels: A Meta-Analysis Study - Eldiana Putri Auliya; Ananta Yudiarso (Psikostudia : Jurnal Psikologi, 2022)
The Perceived Stress Scale, Self-Rating Depression Scale, Academic Stress Scale, and Distress CORE were used to determine the effectiveness of Dance Movement Therapy in lowering stress. A meta-analysis utilizing jamovi 1.6.6 was used as the approach. This research was conducted using a literature evaluation of 11 experimental journals on the effects of Dance Movement Therapy on stress (total n experimental group = 491 and total n control group = 454), for a total of 945 participants. Dance Movement Therapy was shown to be less effective in lowering stress levels (d=0,427), with a medium effect size. According to the findings, Dance Movement Therapy is less successful at reducing stress levels, hence it will be more effective if one type of dance/intervention is used in conjunction with other interventions. Penelitian ini bertujuan untuk melihat efektivitas dari Dance Movement Therapy terhadap penurunan stres yang diukur dengan menggunakan Perceived Stress Scale, Self-Rating Depression scale, Academic stress scale dan Distress CORE. Metode yang digunakan adalah meta-analisis dengan jamovi 1.6.6. Penelitian melalui literatur review 11 jurnal eksperimen mengenai Dance Movement Therapy terhadap stres (total n experiment group = 491; total n control group = 454) sehingga jumlah keseluruhan sebanyak 945. Hasil yang didapatkan ialah Dance Movement Therapy kurang efektif dalam menurunkan tingkat stres (d=0,427; medium effect size). Disimpulkan bahwa Dance Movement Therapy kurang efektif untuk menurunkan tingkat stres sehingga akan menjadi lebih efektif jika menggunakan satu jenis tari/ bentuk intervensi serta ada pendampingan dari intervensi lain.